Analysis of the virtualized teaching in a context of pandemic - Sepúlveda-Irribarra, Cristian; Villegas-Dianta, Adrian; Alcorta-Ramírez, Isaac (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The purpose of the study was to examine the pedagogical practices carried out through ICT, composed by teachers of the Faculty of Education at the University of Las Américas -in pandemic times-. The study is a non-experimental exploratory research with a mixed methodology. The data was collected from a semi-structured interview of 82 open and closed-ended questions. The most important results show that there is an evident tendency to integrate active methodologies, mainly in flipped classroom and the use of learning capsules. Finally, the integration of assessment and collaboration tools prevails.